Fostering inclusive workplaces in Tacloban City employee challenges, needs, and employer-perceived benefits of PWD employment - Dy, Marwyl Joseph; Granados, Bien Angeline; Maureal, Siehr; Mirante, Maria Kyla Mae; Pulga, Mary Zoe
Despite legislative efforts promoting workplace inclusion in the Philippines, persons with physical disabilities continue to face significant challenges in employment, particularly in the private sector. In Tacloban City, an economically growing region, data on inclusive employment remain limited. This study addresses these gaps by examining the challenges faced by employees with physical disabilities, their workplace needs, and the organizational benefits they bring from the employers' point of view. The research aimed to foster inclusivity in Tacloban's private sector and contribute to policy and practice reforms that align with the United Nations Sustainable Development Goals particularly on reducing inequality and ending poverty. Ten participants were selected through purposive and snowball sampling-five employees with physical disabilities and five employers. The study was conducted in private business establishments in Tacloban City utilizing semi-structured interviews and thematic analysis to interpret responses and identify core themes. Findings revealed communication barriers, income insecurity, accessibility issues, difficulties in social interactions, and unreceptive management. Employees expressed needs for assistive technology, fair compensation, improved workplace accommodations, health and wellness support, effective feedback systems, and professional development initiatives. Employers acknowledged benefits such as improved reputation, enhanced employee collaboration, morale, loyalty, increased productivity and overall business performance. The study concluded that despite efforts to promote inclusivity, systemic gaps persist that hinder the complete integration and professional development of these workers. To address these, the study recommends creating barrier-free workplace designs, providing accessible communication tools, equitable pay, inclusive support systems and leadership.